Analisis Keterjangkauan Sekolah Dasar (SD) pada Sekolah Menengah Pertama (SMP) Negeri di Kecamatan Karangmoncol Kabupaten Purbalingga - Layla Lianita N; Sutomo Sutomo; Dhi Bramasta (UM Purwokerto Press, 2022)
In the implementation of the online New Student Admission for public junior high schools in Purbalingga Regency for the 2020/2021 academic year, data was obtained that from 54 public junior high schools that implemented online New Student Admission, there were 29 schools that lacked new students. So that almost all public junior high schools in Purbalingga Regency cannot meet the available quota of new students. Of the 29 schools, there are 4 schools in Karangmoncol District that cannot meet the quota of new students. This research method is carried out by describing the conditions of the research area based on real conditions, namely knowing the number of elementary school graduates and the location of junior high schools against the lack of new students in public junior high schools in Purbalingga Regency. There are 23 elementary schools in the district. Karangmoncol spread over 11 villages, a sample of 1 school was taken in each village. And the results obtained from the secondary school of elementary school students in Karangmoncol District. Of the 329 elementary school students who graduated, 64% continued to junior high school, 24% continued to Madrasah Tsanawiyah, 10% continued to Islamic boarding school and 2% did not continue their education. It can be seen that not all elementary school graduates continue their education to junior high schools in Karangmoncol District. Based on the affordability map of junior high schools in elementary schools in Karangmoncol District, the unfulfilled quota of new students in 2020/2021 can be seen from the affordability based on Chiara's theory (1975) with a spatial radius of 800 m to 1200 m State Junior High School organizers for the affordability of the location of State Junior High Schools in Karangmoncol District. State 800 m to 1200 m for the affordability of the location of the State Junior High School in Karangmoncol District.